XRT- Exploring Runtime for .NET Architecture and Applications - Tillmann, Nikolai; Schulte, Wolfram (Electr. Notes Theor. Comput. Sci., 2006)
XRT – Exploring Runtime – is an exploration framework for programs represented in Microsoft's common intermediate language (CIL). Processing .NET managed assemblies, it provides means for analyzing, rewriting, and executing the rewritten program. Whereas XRT's representation of state allows for arbitrary exploration strategies, it is particularly optimized for transactional exploration, where a transaction may consist of many instruction steps. XRT supports extensions, and one such extension is a module for symbolic exploration which captures the complete domain of safe CIL. Current applications of XRT are in the area of testing, namely parameterized unit testing and state-space exploration for model-based testing. This paper gives an overview of the architecture of XRT and outlines the applications.